2015
DOI: 10.15171/hpp.2015.024
|View full text |Cite
|
Sign up to set email alerts
|

The Technical Quality of Delivered Care for People with Inflammatory Bowel Disease in Tabriz Gastroenterology Clinics

Abstract: Background: The Inflammatory Bowel Disease (IBD) is considered as one of the chronic diseasesre-quiring complicated treatment. This study aimed to assess technical quality of providing care for pa-tients with IBD. Methods: This cross-sectional study was conducted on 94 people with IBD using interviews and simple random sampling methods in Gastroenterology, Endoscopy and clinic of Imam Reza Hospital and Golgasht Clinic in Tabriz in 2012. The data collection tool was a researcher-designed questionnaire whose v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“… 11 However, some of the patients in this study reported that dietary advice provided by healthcare professionals was often broad, generalised and even contradictory. A previous cross‐sectional study 12 on the quality of care for patients with IBD reported that satisfaction was the lowest for ‘dietary advice from a dietitian’. Furthermore, although gastroenterologists are experts in the function of the gastrointestinal tract, most of them are not experts in nutritional science.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 However, some of the patients in this study reported that dietary advice provided by healthcare professionals was often broad, generalised and even contradictory. A previous cross‐sectional study 12 on the quality of care for patients with IBD reported that satisfaction was the lowest for ‘dietary advice from a dietitian’. Furthermore, although gastroenterologists are experts in the function of the gastrointestinal tract, most of them are not experts in nutritional science.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, some of the patients in this study reported that dietary advice provided by healthcare professionals was often broad, generalised and even contradictory. A previous cross-sectional study 12 on the quality of care for patients with IBD reported that satisfaction was the lowest for 'dietary advice from a This factor may lead to increased confusion and bewilderment amongst patients about complex dietary choices. According to previous studies, 13,14 many patients with IBD employ an elimination diet to avoid disease exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…It is a public recognition by accrediting bodies to hospitals compliant with a desirable set of standards that serve as a guide for excellence 2. These standards are created to meet the need for quality care performance ensuring compliance with the optimum requirements, which are evaluated by an objective expert survey team 3. A theoretical approach for accreditation has been proposed by Desveaux et al,4 who hypothesized 3 stages seeking a visible impact on health care quality: (1) alignment of accreditation with the organizational vision, mission, and values, called “coherence”; (2) “buy-in” for acceptance of positive changes by champions seeking better care; (3) “action” by implementing quality improvement projects in response to accreditation findings.…”
mentioning
confidence: 99%